Content validation of a Critical Appraisal Tool for Reviewing Analgesia Studies (CATRAS) involving subjects incapable of self-reporting pain - Warne, Leon N. (2018)
Introduction: This article reports the content validation of a Critical Appraisal Tool designed to Review the quality of Analgesia Studies (CATRAS) involving subjects incapable of self-reporting pain and provide guidance as to the strengths and weakness of findings. The CATRAS quality items encompass 3 domains: level of evidence, methodological soundness, and grading of the pain assessment tool. Objectives: To validate a critical appraisal tool for reviewing analgesia studies involving subjects incapable of self-reporting pain. Methods: Content validation was achieved using Delphi methodology through panel consensus. A panel of 6 experts reviewed the CATRAS in 3 rounds and quantitatively rated the relevance of the instrument and each of its quality items to their respective domains. Results: Content validation was achieved for each item of the CATRAS and the tool as a whole. Item-level content validity index and kappa coefficient were at least greater than 0.83 and 0.81, respectively, for all items except for one item in domain 2 that was later removed. Scale-level content validity index was 97% (excellent content validity). Conclusions: This 67-item critical appraisal tool may enable critical and quantitative assessment of the quality of individual analgesia trials involving subjects incapable of self-reporting pain for use in systematic reviews and meta-analysis studies.